1992
DOI: 10.1038/jcbfm.1992.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indomethacin on Myogenic Contractile Activation and Responses to Changes in O2 and CO2 in Isolated Feline Cerebral Arteries

Abstract: Summary:We used an isolated, pressurized, and per fused feline middle cerebral artery preparation to mea sure how changes in intraluminal pressure and alterations in O2 and CO2 affect vessel diameter and myogenic con tractile activation before and after treatment with indo methacin (I ND). Vessel diameters were measured over the pressure range 60-140 mm Hg. The arteries were then exposed to low O2 (50 torr) and/or high CO2 (65 torr) and diameters remeasured over the same range. Under con trol conditions, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In several studies and in different species, including humans, indomethacin has been shown to inhibit the response to hyper‐ capnia in a variety of vascular beds; 40–45 however, the effects of indomethacin are unrelated to the inhibition of prostanoid production 44,46 …”
Section: Discussionmentioning
confidence: 99%
“…In several studies and in different species, including humans, indomethacin has been shown to inhibit the response to hyper‐ capnia in a variety of vascular beds; 40–45 however, the effects of indomethacin are unrelated to the inhibition of prostanoid production 44,46 …”
Section: Discussionmentioning
confidence: 99%
“…12 Although the standard therapy observed before and during indomethacin infusion did not appear to effect significant changes, the fact that in three cases mannitol reestablished its action on ICP and CPP during indomethacin infusion was consistent with the view that indomethacin could have a beneficial effect on cerebral autoregulation. 9 Third, it is also probable that the beneficial effects of indomethacin infusion could be due to nonvascular actions on baseline ICP in pathological conditions such as ischemic and vasogenic edema. 1,4,14 Decreased production of cerebrospinal fluid following endothelin potentiation has been recently demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…22 Alternative mechanisms include interference with the regulation of cerebrovascular tone mediated by extracellular pH, 23 a reduction of cerebral temperature, 24 as well as a direct non-prostaglandin-mediated vasoconstrictive effect. 25 Our study was not designed to dissect this complexity, although we did show evidence of decreased prostanoid formation without effects on body temperature.…”
Section: Discussionmentioning
confidence: 99%